2007
DOI: 10.1038/sj.ki.5002568
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria in oxidative and nitrosative stress during ischemia/reperfusion in the rat kidney

Abstract: Reoxygenation following ischemia causes tissue oxidative stress. We studied the role of oxidative stress caused by kidney ischemia/reperfusion (I/R) on the mitochondria of renal tissue slices. I/R caused the mitochondria to be swollen, fragmented, and have lower membrane potential. The mitochondria generated more reactive oxygen species (ROS) and nitric oxide (NO) in situ as measured by fluorescence of ROS- and NO-sensitive probes. Infusion of lithium ion, an inhibitor of glycogen kinase synthase-3, caused pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
154
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(166 citation statements)
references
References 59 publications
(70 reference statements)
6
154
0
6
Order By: Relevance
“…26 Interestingly, differences in PT and DT signal were reported in vivo during an investigation of the excretion of a fluorescent substrate for organic cation transport in the kidney. 27 In addition, a study of ⌬ m in live kidney slices using confocal imaging of tissue loaded with tetramethyl rhodamine ethyl ester (TMRE) showed heterogeneity in signal among different cell types, 3 but the investigators did not comment on the nature of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…26 Interestingly, differences in PT and DT signal were reported in vivo during an investigation of the excretion of a fluorescent substrate for organic cation transport in the kidney. 27 In addition, a study of ⌬ m in live kidney slices using confocal imaging of tissue loaded with tetramethyl rhodamine ethyl ester (TMRE) showed heterogeneity in signal among different cell types, 3 but the investigators did not comment on the nature of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…86 Finally, rats that were injected 30 minutes before ischemia-reperfusion with lithium displayed reduced levels of renal oxidative stress, because they exhibited a diminished mitochondrial membrane depolarization and reactive oxygen species (ROS) production. 13 In addition, a 30-day pretreatment of rats with lithium reduced renal damage induced by ischemia-reperfusion, which was shown by the reduction in BUN and serum creatinine and the improved preservation of the tubular structure. 20 Remarkably, lithium treatment of mice 8 hours after the onset of ischemiareperfusion was also effective in reducing kidney injury, because these mice exhibited less necrosis and a faster recovery of serum creatinine levels.…”
Section: Lithium Reduces Kidney Damage In Various Nephropathy Modelsmentioning
confidence: 99%
“…10,11 In contrast to these adverse effects of lithium treatment, accumulating evidence suggests that the administration of low lithium amounts (,0.6 mM in blood) improves kidney function in different animal nephropathy models. Single-bolus injections or short-term treatment (,1 week) of lithium reduced adriamycin-, LPS-, cisplatin-, gentamicin-, and ischemiainduced AKI, [12][13][14][15][16][17][18] whereas prolonged treatment ($1 month) alleviated kidney damage because of ischemia-reperfusion, hypertension, and the autoimmune disease lupus erythematosus. [19][20][21] To understand these opposing findings, we will first present an overview of renal lithium handling and then, discuss the molecular pathways underlying the toxic and potential therapeutic effects of lithium in the kidney.…”
mentioning
confidence: 99%
“…Although it is precisely not known how mPT contributes to PTN formation, mitochondria have been shown to produce reactive oxygen species (ROS), as well as NO, 57 and induction of mPT has been suggested as one mechanism for such mitochondrial ROS and NO generation. 58,59 Moreover, as peroxynitrite, largely generated in mitochondria, is the major free radical responsible for PTN, 53 it is likely that superoxide and NO produced by mPT might lead to PTN. Consistent with this view, Burke et al 60 have shown blockade of PTN by CsA in mouse hepatocytes exposed to chloroform.…”
Section: This Study Demonstrates That Exposure Of Primary Cultures Ofmentioning
confidence: 99%